Tropical peatlands management and climate change: a case study in Sumatra, Indonesia - Murdiyarso, Daniel; Suryadiputra, I.N.; Wahyunto (International Peat Society, 2004)
Tropical peatland is an important terrestrial carbon pool and habitat of endemic species that requires sustainable management for the benefit of local livelihoods and global climate. The size of carbon stocks and accumulation are staggering but there is no clear and easy access to markets for tropical peatland conservation. Meanwhile the benefits of environmental services are largerly enjoyed by national wealthier and global beneficieries. This paper demonstrates the loss of carbon at various sites as part of development opportunity at various peatland environments and social structure. Peatland development in the tropics including Indonesia is driven by the increasing need for land, food, and fiber under the pressure of population growth. In Sumatra, where peatland covered an area of 7.2 Mha in 1990 was estimated that it has reduced to 6.5 Mha in the recent survey in 2002. The common practice in peatland development is deforestation followed by extensive drainage before settlement and agricultural development taking place. Under such conditions it is estimated that Sumatran peatlands have released 3.47 Gt C contributing to global climate change, in addition to the emerging local environmental problems, such as flooding and drought leading to soil acidity and fires.